The Effect of STEM-PjBL and Discovery Learning on Improving Students' Problem-Solving Skills of Impulse and Momentum Topic - Purwaningsih, E.; Sari, S. P.; Sari, A. M.; Suryadi, A. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
This study aims to investigate the effect of Science, Technology, Engineering, and Mathematics-Project Based Learning (STEM-PjBL) and discovery learning on students' problem-solving abilities. The research is a Quasi-Experiment with a Nonequivalent Pretest-Posttest Control Group Design. The participants involved are 53 students of class X from a high school in Malang, where 28 students studied with STEM-PjBL, and 25 students studied with discovery learning. This research was conducted on the subject of impulse and momentum. In this analysis, researchers have developed problem-solving tools with a particular field approach to impulse and momentum topics in order to obtain an instrument with a reliability ofÃ‚Â 0.81. This instrument collects student problem-solving data before and after learning both in the experimental class and in the comparison class. Problem-solving skills data were analyzed using descriptive statistics and inferential statistics. The results showed a significant difference in the scores of students' problem-solving abilities in the experimental class and the comparison class (p<0.05). The problem-solving ability in the experimental class (Md=78.74) was higher than the comparison class (Md=70.00). In STEM-PjBL learning, students are better trained and challenged to solve problems in everyday life. Compared to the comparison class, learning in the experimental class is more able to accommodate students' ideas and make students more interested in learning. In conclusion, STEM-PjBL has a significant positive effect on improving students' problem-solving abilities rather than discovery learning.